Evolutions and Opportunities of Business Education in the Context of Educational Reform from the Digital Age - Bogdan Onete; Doru Pleşea; Ioana Teodorescu; Alice Cîrstea (Amfiteatru Economic)
Education and training research for business environment has become an important subject to debate in nowadays, because it allows the design of scenarios that contribute to economic and social development. In this paper, we propose to analyse the evolution of business educational models, in terms of new forms of learning: e-learning and MOOC. It will also be analysed the impact of educational methods in the virtual environment in the classic educational system. Last but not least there will be outlined the perspectives and opportunities of business education in the context of educational reform at European and global level. In this regard, it will be drawn the direction and position of Romania towards the reorganization of business education model.